Percutaneous closure of perimembranous ventricular septal defects associated with septal aneurysm in adults - Oktay Ergene; Nihan Kahya Eren; Cem Nazlı; Hamza Duygu; Uğur Kocabaş (KARE Publishing, 2015)
Objective: Percutaneous closure of perimembranous ventricular septal defects (pmVSD) has become an accepted alternative to surgical closure in selected cases. However, closure of pmVSDs associated with septal aneurysm is more challenging. We report our experience of device closure of pmVSDs associated with septal aneurysm. Methods: Between 2008 and 2012, percutaneous closure of pmVSD associated with septal aneurysm was attempted in 11 adult patients in our institution. The patients were followed up at 1, 3, 6, and 12 months after the procedure. Results: Mean age of the patients (64% male, 36% female) was 36.2+-1.3 years. Diameter of the left and right ventricular openings of the aneurysm measured by ventriculography was 13.5+-5.6 mm and 5.9+-2.2 mm, respectively. The defect was occluded with Amplatzer pmVSD Occluder in 4 patients, Amplatzer Muscular Ventricular Septal Defect Occluder in 4 patients, Amplatzer Duct Occluder I in 1 patient, and Amplatzer Duct Occluder II in 2 patients (AGA Medical Corp., Plymouth, MN, USA). The procedure was succesfull in all patients. Mean follow-up time was 22+-1.9 months. There was no device- or procedure-related complications at the acute setting or midterm follow-up. Conclusion: Percutaneous closure of pmVSDs associated with aneurysm is more challenging than that of simple defects. The selection of the device type and size should be made according to the configuration and size of the aneurysm and defect.